2005
DOI: 10.1097/00004010-200501000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Health Information System Adoption in American Hospitals

Abstract: The study concludes that hospital organizational and financial factors influence on hospitals' strategic adoption of clinical, administrative, and managerial information systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 25 publications
9
96
2
2
Order By: Relevance
“…25 In addition to the risk adjustment, we also controlled for hospital-level variables, such as bed size, ownership type, teaching affiliation, system membership, network participation, the number of staffed beds per full time equivalent registered nurses, percentage Medicare patients, percentage Medicaid patients, capitation-based reimbursement, market competitiveness, rural or urban hospital, and hospital region. 26,27 Given that there were more than 40 independent variables to be modeled, we used the preliminary regression analysis for detecting multicollinearity among independent variables in the multivariable models. 28 For example, teaching hospital status was not included in the multivariable model because it was highly correlated to bed size; percentage of Medicare patients was not included due to its high correlation with percentage of Medicaid patients.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition to the risk adjustment, we also controlled for hospital-level variables, such as bed size, ownership type, teaching affiliation, system membership, network participation, the number of staffed beds per full time equivalent registered nurses, percentage Medicare patients, percentage Medicaid patients, capitation-based reimbursement, market competitiveness, rural or urban hospital, and hospital region. 26,27 Given that there were more than 40 independent variables to be modeled, we used the preliminary regression analysis for detecting multicollinearity among independent variables in the multivariable models. 28 For example, teaching hospital status was not included in the multivariable model because it was highly correlated to bed size; percentage of Medicare patients was not included due to its high correlation with percentage of Medicaid patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors may influence the adoption and acceptance of these systems. Several studies have investigated these factors [1,11,12]. According to Anderson et al [13] since physicians are the main front line users of HIS, their resistance is one of the important factors affecting implementation of this system.…”
Section: Introductionmentioning
confidence: 99%
“…According to Anderson et al [13] since physicians are the main front line users of HIS, their resistance is one of the important factors affecting implementation of this system. Other researches [12,10,14,15] addressing failure factors showed that obstacles such as time constraints, security and privacy risk, lack of an adequate policy regarding medical IT, non-applicability with regard to patient characteristics, and complex clinical settings are among culprits. Similarly, lack of financial resources and high costs; poor management and bureaucracy; poor staff IT competency; lack of qualified IT personnel and lack of awareness of HIT (health information technology) values, are barriers to the adoption of health information technology in Arab countries' hospitals [16].…”
Section: Introductionmentioning
confidence: 99%
“…Hospital characteristics, such as economies of scale, payer mix, ownership, urban or rural location, financial performance, and teaching status are found to be strong predictors of technology adoption [13][14][15][16][17][18][19]. Investigated environmental factors include competition, reimbursement policies [20,21], managed care penetration [22,23], insurance market characteristics [24], and the technology adoption behavior of neighboring hospitals [12].…”
Section: Introductionmentioning
confidence: 99%